The Effect of Corporate Social Responsibility on Employee Performance with Job Satisfaction and Employee Engagement as Mediation Variables (Study on employees of PT. Salim Ivomas Pratama Tbk PKS Sungai Dua in Pekanbaru, Riau) - Anita Dwi Rahma (Universitas Muhammadiyah Sorong, 2023)
The purpose of this study was to analyze the effect of corporate social responsibility on employee performance where job satisfaction and employee engagement are mediated variables. Research investigating social responsibility improves employee performance through job satisfaction and employee engagement. Collecting data using a questionnaire. The model is tested by using the outer model and inner model. A sample of 124 employees at PT. Salim Ivomas Pratama Tbk Sungai Dua PKS in Pekanbaru, Riau. The results of research on social responsibility have a positive effect on employee performance, t count > Z score 1.96 worth 2.142 and p value <0.05 worth 0.033; In addition, job satisfaction mediates the relationship of social responsibility to employee performance, t statistics > Z score 1.96 worth 2.511 and p value <0.05 worth 0.012, while the indirect effect is t value > Z score 1.96 worth 2.419 and p value < 0.05 worth 0.016. Employee engagement mediates the relationship of social responsibility to employee performance, t value > Z score 1.96 worth 2.208 and p value < 0.05 worth 0.028, while the indirect effect is t value > Z score 1.96 worth 2.199 and p value < 0.05 is worth 0.028. The limitations of this study are the limited sample; Future research is expected to be carried out with a larger sample.